PENGARUH KOMPETENSI GURU, KEPEMIMPINAN KEPALA SEKOLAH, DAN SARANA PRASARANA PENDIDIKAN TERHADAP KINERJA GURU SEKOLAH MENENGAH KEJURUAN (SMK) SWASTA DI KECAMATAN KEBUMEN TAHUN PELAJARAN 2013/2014 (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
Influence of Teacher Competency, Principal’s Leadership, and Infrastructure of education toward Teacher Education Vocational School (SMK) in District Kebumen of academic year 2013/2014. The study aims to determine: a) The Influence of teacher competence, Principal’s leadership, and education infrastructure on teacher performancer, b) The Influence of teacher competence toward teacher performance, c) The Influence of school leadership toward teacher performance, d) The Influence of infrastructure of education toward teacher performance .The study was conducted in District Kebumen in the academic year 2014. This research is a quantitative one using survey method. The population of this research is 143 private vocational school teachers in District Kebumen. The sample of this research is 107 teachers and was taken by using proportional random sampling techniques. The data were Collected by using a questionnaires. Technical analysis of the data used the F test or ANOVA followed by hypothesis testing individual partial test (t-test). Processing data used SPSS v. 16. All Effective contribution was taken fram the analysis result of the value of the determination coefficient multiplied by 100 %, and the partially effective contribution by multiplying of the Standarted value Coefficiens Beta with Zero- order Correlation values multiplied by 100 % for each independent variable.   The results show that: (1) there is a positive and significant effect of teacher competence, school leadership, and education infrastructure jointly on the performance of private vocational school teachers in District Kebumen of 31.8%; (2) there is a positive and significant influence on the performance of 6.75%; (3) there is a positive and significant effect of 12.18%; (4) there is a positive and significant effect of infrastructure on the performance of 12.82%.Based on the results of this study suggested that the implications for improving the performance of vocational teachers can be done by increasing the competence of teachers, remind the quality of school leadership as well as complement the educational infrastructure needs that support learning.